THE EFFECT OF ATTRACTION, AMENITIES, AND ACCESSIBILITY TOWARD TOURIST SATISFACTION IN CANDI PRAMBANAN - Adhitama, Boni Bonar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2021)
Tripadvisor is a popular website that collects various tourist reviews about a tourist spot that users have previously visited. Reviews are important factors that influence a tourist's decision or motivation to travel to a place. Prambanan Temple is one of the tourist attractions that has been given many reviews on TripAdvisor. Looking at this aspect, this study utilizes the reviews of foreign tourists which aim to increase visitor satisfaction and economic activities at Prambanan Temple. This study used a sample of 250 respondents by taking the reviews on TripAdvisor about Prambanan Temple. The research data is obtained directly from the internet using data mining for further analysis. Data analysis in this study used the content analysis method. The results of the content analysis in this study are information and suggestions to improve visitor satisfaction and economic activity for the Prambanan Temple to be better. The results of testing the three hypotheses can be concluded that attractions, amenities, and accessibility have an effect on tourist satisfaction.Keywords: Tourism, Big Data, Data Mining, TripAdvisor, Content Analysis, Tourist Satisfaction, Attractions, Amenities, Accessibilities.